On the Weak Solution to a Fractional Nonlinear Schrödinger Equation - Zujin Zhang; Xiaofeng Wang; Zheng-an Yao (Abstract and Applied Analysis)
We obtain the existence of a global weak solution to a fractional nonlinear Schrödinger equation by the Galerkin method. Its uniqueness is also discussed. In our proof, we use harmonic analysis techniques and compactness arguments.